1976
DOI: 10.1056/nejm197607012950101
|View full text |Cite
|
Sign up to set email alerts
|

Value and Limitations of Thallium-201 Scintigraphy in the Acute Phase of Myocardial Infarction

Abstract: We examined the diagnostic usefulness of thallium-201 scintigraphy in 200 patients with acute myocardial infarction. The scintiscans showed a defect, suggesting infarction in 165. In all 44 patients studied iwthin six hours after onset of symptoms the scintiscans indicated a defect. Frequency of positive scans was significantly higher (90 of 96) in patients studied within 24 hours after onset than in those (75 of 104) studied later (p less than 0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(19 citation statements)
references
References 7 publications
0
16
0
1
Order By: Relevance
“…Of the isotopes suitable for gamma camera imaging, 201T1 is most widely used but good quality images can be obtained using 129Cs (Romhilt et al, 1973), particularly in association with blood background correction techniques (Rothman et al, 1974). In contrast to 99Tcm PYP ionic tracers can demonstrate infarction soon after onset of symptoms (Wackers et al, 1976). Even transient defects present only on exercise can be shown in patients with angina pectoris using tracers such as 43K and 201TI which have a rapid myocardial uptake.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of the isotopes suitable for gamma camera imaging, 201T1 is most widely used but good quality images can be obtained using 129Cs (Romhilt et al, 1973), particularly in association with blood background correction techniques (Rothman et al, 1974). In contrast to 99Tcm PYP ionic tracers can demonstrate infarction soon after onset of symptoms (Wackers et al, 1976). Even transient defects present only on exercise can be shown in patients with angina pectoris using tracers such as 43K and 201TI which have a rapid myocardial uptake.…”
Section: Discussionmentioning
confidence: 97%
“…Any estimation of infarct size from perfusion defects entails subjective assessment of the original mass of myocardium. Such estimates necessarily include old as well as recent infarction and it has been reported that perfusion defects resulting from myocardial infarction tend to diminish or disappear over the first 24 hours after infarction (Wackers et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…201TI is currently the best of these indicators because of its favourable physical and biological properties Feller and Sodd, 1975;Lebowitz et al, 1975). The reliability and limitations of thallium scintigrams have been assessed by many authors Wackers et al, 1975;Bailey et al, 1976;Mueller et al, 1976;Pachinger et al, 1977;Wackers et al, 1976). Most of these reports deal with a qualitative correlation between 201TI-imaging and conventional contrast angiocardiographic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Specificity may be improved by the use of indium-III labelled monoclonal antimyosin antibodies.48-50 Access to radionuclide scanning is not generally available to accident and emergency departnents in the UK. Scanning is best performed under cardiological supervision.…”
Section: Radionuclide Scansmentioning
confidence: 99%